Socio-Economic Study on Awareness And Readiness of SMEs in Adopting The Green Economy Model in Sumedang - Fahreza, Mohammad; Maryam, Siti (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
Indonesia struggles with significant food and plastic waste. Restaurants and cafés in Sumedang Regency (KBLI 56) are major contributors but could spearhead the green economy transition. This study examines the awareness and readiness of food‑service SMEs to adopt green practices by integrating the Technology–Organization–Environment (TOE) framework with Pro‑Environmental Planned Behavior (PEPB). A cross‑sectional survey of owner‑managers was analysed using PLS‑SEM; after confirmatory factor analysis, nineteen indicators remained and the model achieved acceptable fit. Results show that access to green finance (β = 0.852, p < 0.001) and institutional pressure (β = 1.598, p < 0.001) significantly enhance SMEs’ digital capability, whereas environmental knowledge and sustainability attitude have no direct effect. Digital capability strongly drives green‑economy adoption (β = 0.769, p = 0.046) and fully mediates the impact of financial access and institutional pressure on adoption; direct paths from knowledge, attitude or finance to adoption are insignificant. These findings highlight an attitude–behaviour gap and underscore the need to build digital capability through funding and normative pressures. Policy implications include bundling green loans with digital training and establishing gentle regulatory norms to prepare SMEs for sustainable operations. Keywords: green-economy adoption; digital capability; institutional pressure; SMEs (KBLI 56); Sumedang